2022
DOI: 10.1155/2022/1406820
|View full text |Cite
|
Sign up to set email alerts
|

Huayu Jiedu Fang Protects Ovarian Function in Mouse with Endometriosis Iron Overload by Inhibiting Ferroptosis

Abstract: Endometriosis (EM) is a common chronic inflammatory disease in women. Sampson’s retrograde menstruation theory is the most widely accepted theory of EM pathogenesis. The periodic bleeding of ectopic lesions is an important pathological feature of this disease, and the occurrence and progression of EM are closely associated with the iron overload caused by ectopic lesions. However, animal models that simulate menstrual-blood reflux and hemorrhage from EM lesions are lacking. In this study, we performed intraper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…When SLC7A11, the major functional subunit of system Xc − , is deficient or has reduced activity, GSH synthesis is reduced, causing reduced expression and activity of GPX4, resulting in the inability of cells to effectively scavenge lipid peroxides, and finally oxidative damage to the cell membrane, leading to cell ferroptosis 42 . Previous studies have reported a correlation between GSH, GPX4 and ovarian dysfunction; however, few studies have focused on the correlation between SLC7A11 and POI [43][44][45][46] . Therefore, we mainly selected SLC7A11 to further validate the association of POI and ferroptosis, but we still validated the expression of GPX4 in animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…When SLC7A11, the major functional subunit of system Xc − , is deficient or has reduced activity, GSH synthesis is reduced, causing reduced expression and activity of GPX4, resulting in the inability of cells to effectively scavenge lipid peroxides, and finally oxidative damage to the cell membrane, leading to cell ferroptosis 42 . Previous studies have reported a correlation between GSH, GPX4 and ovarian dysfunction; however, few studies have focused on the correlation between SLC7A11 and POI [43][44][45][46] . Therefore, we mainly selected SLC7A11 to further validate the association of POI and ferroptosis, but we still validated the expression of GPX4 in animal experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Excess iron decreases the expression of solute carrier family 7 member 11 (SLC7A11; a light-chain subunit of xCT) and GPX4, which efficiently increases susceptibility to ferroptosis ( 61 ). Blood injection results in GPX4 protein depletion in murine models with endometriosis iron overload ( 62 ). In fact, it has been reported that GPX4 expression in the early secretory phase is markedly lower in the eutopic endometrium of women with endometriosis compared with those with normal endometrium ( 63 ).…”
Section: Molecular and Regulatory Network Mechanisms Controlling Ferr...mentioning
confidence: 99%
“…First, it is well known that the SLC3A2/SLC7A11/Nrf2/GPX4 pathway controls ferroptosis ( 60 ). It has been reported that iron administration reduced GPX4 levels in rat models (early stages of endometriosis) ( 62 ). This result suggests the importance of ferroptosis induction for cell survival during the early stages of endometriosis development.…”
Section: Molecular and Regulatory Network Mechanisms Controlling Ferr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, exogenous ferroptosis inducer-induced ferroptosis inhibits oocyte meiosis by increasing oxidative stress, inducing mitochondrial dysfunction, triggering autophagy splitting process and affecting oocyte quality [ 127 ]. Conversely, the inhibition of ferroptosis might not only inhibit the progression of endometriosis, but also improve the adverse effects of iron overload on ovarian function, thereby improving fertility and becoming a therapeutic approach for endometriosis-related infertility [ 128 ].…”
Section: Ferroptosis and Endometriosis-related Infertilitymentioning
confidence: 99%